A new geodemographic classification of commuting flows for England and Wales. Issue 4 (3rd April 2018) - Hincks, Stephen; Kingston, Richard; Webb, Brian; Wong, Cecilia
ABSTRACT: This paper aims to contribute to the area of geodemographic research through the development of a new and novel flow-based classification of commuting for England and Wales. In doing so, it applies an approach to the analysis of commuting in which origin-destination flow-data, collected as part of the 2011 census of England and Wales, are segmented into groups based on shared similarities across multiple demographic and socioeconomic attributes. k -Means clustering was applied to 49 flow-based commuter variables for 513, 892 interactions that captured 18.4 million of the 26.5 million workers recorded as part of the 2011 census of England and Wales. The final classification resulted in an upper-tier of nine 'Supergroups' which were subsequently partitioned to derive a lower-tier of 40 'Groups'. A nomenclature was developed and associated pen portraits derived to provide basic signposting to the dominant characteristics of each cluster. Analysis of a selection of patterns underlying the ninefold Supergroup configuration revealed a highly variegated structure of commuting in England and Wales. The classification has potentially wide-ranging descriptive and analytical applications within research and policy domains and the approach would be equally transferable to other countries and contexts where origin-destination data are disaggregated based on commuter characteristics.